Literatura y nacionalismo : la novela colombiana de J. A. Osorio Lizarazo (2009)
ABSTRACT: The reflection on nationalism and literature is an alternative to the common reading of Colombian literary studies, sociology and historiography, which interpret J. A. Osorio Lizarazo novels related to urban scenarios. This paper explores the role of nationalism in Osorio Lizarazo’s narrative, his conception of the novel as an expression —at the cultural level— of the political unity represented by the State, and describes how to understand his work in the context of nationalist practices and discourses associated to policies, institutions and devices aimed to construct a mass culture in Colombia.